2010
DOI: 10.1016/j.socscimed.2010.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Compared to whom? Subjective social status, self-rated health, and referent group sensitivity in a diverse US sample

Abstract: Emerging research has revealed that subjective social status (SSS), or how people perceive their position in the social hierarchy, is significantly associated with multiple health outcomes. Yet few studies have examined how this association is affected by the person or group to whom respondents are comparing themselves. While previous studies have used distal referent groups when assessing SSS, scholars have suggested that individuals may prefer to make comparisons to those who share similar characteristics to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
119
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 45 publications
8
119
2
1
Order By: Relevance
“…The study of differences in health between European countries proved that in all of the analysed European countries, including Poland, selfassessment of health increases with income. This is similar to the studies of L. S. Wolff et al [38] concerning the USA. According to these studies, self-rated health was dependent on household income, education, home ownership, and race/ethnicity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The study of differences in health between European countries proved that in all of the analysed European countries, including Poland, selfassessment of health increases with income. This is similar to the studies of L. S. Wolff et al [38] concerning the USA. According to these studies, self-rated health was dependent on household income, education, home ownership, and race/ethnicity.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the presented study concerning Eastern Poland generally correspond to the results of studies from other countries (Norway, Hungary, South Africa, USA and Netherlands), and indicate a relationship between the socioeconomic position, and self-assessment of health status [35,36,37,38,39,7]. Research conducted by K. M. Olsen and S. A. Dahl [13] concerning the differences in the health of residents of 21 European countries showed that the health status of the population in the analysed countries depended on a variety of political, socio-economic and behavioural characteristics.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…While many of the studies focused on select populations, such as pregnant women (Reitzel et al, 2007), adolescents (Quon and McGrath, 2014), older adults (Garbarski, 2010), or civil service workers (Singh-Manoux et al, 2003, relatively few used representative samples of the general population (Nobles et al, 2013;Sakurai et al, 2010;Wolff et al, 2010). Understanding the interplay of objective and subjective SES, however, requires samples that are free from selection bias, including all SES groups of a population, as associations found in restricted samples might misrepresent those apparent in the general population.…”
Section: The Subjective Ses-health Relationshipmentioning
confidence: 99%
“…The relationship between objective and subjective socioeconomic status (SES) is a classic topic within sociology (Evans and Kelley, 2004;Lindemann and Saar, 2014;Marx, 1976) that has recently resurfaced in public health research (Adler, 2013;Nobles et al, 2013;Singh-Manoux et al, 2005;Wolff et al, 2010). While sociological research on the issue long focused on class conflict and the potential for social revolution, public health research has discovered a robust association between subjective SES and a diverse range of health outcomes, usually over and above the influence of objective measures of social status.…”
Section: Introductionmentioning
confidence: 99%